2017
DOI: 10.18632/oncotarget.21117
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of the association between estrogen receptor of alpha polymorphisms and the risk of prostate cancer: evidence from a meta-analysis

Abstract: We performed a meta analysis to access the relationship of estrogen receptor of alpha (ESRα) polymorphisms with the risk of prostate cancer (PC). Twenty-four case-control studies (including 5477 cases and 10708 controls) were recruited for meta-analysis. The strongest association with the risk of PC was observed between ESRα rs9340799 and rs2234693 under the two genotypic models of allele and codominance in the overall population (p < 0.05). Under the subgroup analysis of ethnicity, we observed that ESRα rs934… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Thus, this study confirms that there is no correlation between ERα and PCa expression. However, according to a review study by Bonkhoff et (16). In this study, it was confirmed that ERα is not related to PCa development.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, this study confirms that there is no correlation between ERα and PCa expression. However, according to a review study by Bonkhoff et (16). In this study, it was confirmed that ERα is not related to PCa development.…”
Section: Discussionsupporting
confidence: 67%
“…It was reported that substitution of T by C led to loss of PvuII restriction site , and the resulted C allele produced myb transcription factor binding site, significantly increasing transcription compared to the T allele (Herrington et al, 2002). Several diseases, including BC (Zhang et al, 2015;Zhang et al, 2018), endometrial cancer (Ashton et al, 2009), prostate cancer (Li et al,,2017), Alzheimer's disease (Cheng et al, 2014), endometriosis and leiomyoma (Hsieh et al, 2007), and hepatocellular and gallbladder cancer (Sun et al, 2015) were assessed for probable association with PvuII polymorphism. In this study, no genetic association was found between PvuII polymorphism and BC risk.…”
Section: Discussionmentioning
confidence: 99%
“…ESR1 regulates cell proliferation and differentiation by a hormonal mechanism known as the paracrine mechanism, which is tightly associated with BC development [10]. Genetic variants in human ESR1 have been extensively studied for their role in the susceptibility to various malignancies (e.g., lung, breast, prostate, cervical, ovarian, leiomyoma, gallbladder, and endometrial cancers) in people of multiple ethnicities [11][12][13][14][15]. Two frequently studied polymorphisms (rs2234693 and rs9340799) in the ESR1 gene are found to be associated with the development of BC [16,17].…”
Section: Introductionmentioning
confidence: 99%